Pengaruh manajemen waktu dan motivasi belajar terhadap prestasi belajar mahasiswa pendidikan ekonomi di masa pandemi - Zefanya Devasmara Yuan Widhita; Mintasih Indriayu; Dewi Kusuma Wardani (Jurnal Pendidikan Ekonomi (JUPE), 2023)
The success of students in participating in learning activities during lectures can be seen from their learning achievements. However, during the Covid-19 pandemic the implementation of learning experienced several problems. This study aims to determine the effect of time management and learning motivation on Economics Education students' learning achievement during a pandemic. The research method used is descriptive quantitative. The sampling technique used proportionate stratified random sampling, with a sample of 216 respondents. Data collection techniques using online questionnaires and documentation. The data analysis technique in this study is multiple linear regression analysis. The results showed that: (1) time management had a positive effect on Economic Education students' learning achievement during the pandemic, (2) learning motivation had a positive effect on Economics Education students' learning achievement during the pandemic, (3) time management and learning motivation had a positive effect simultaneously on the learning achievement of Economics Education students during the pandemic.